2011
DOI: 10.1002/btpr.609
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal myotube integration with planar microelectrode arrays in vitro for spatially selective recording and stimulation: A comparison of neuronal and myotube extracellular action potentials

Abstract: Microelectrode array (MEA) technology holds tremendous potential in the fields of bio-detection, lab-on-a-chip applications, and tissue engineering by facilitating non-invasive electrical interaction with cells in vitro. To date, significant efforts at integrating the cellular component with this detection technology have worked exclusively with neurons or cardiac myocytes. We investigate the feasibility of using MEAs to record from skeletal myotubes derived from primary myoblasts as a way of introducing a thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 24 publications
0
26
1
Order By: Relevance
“…A small fraction of recorded individual gMμEs comprised FPs that were most likely generated by a number of adjacent myotubes. It should be noted that the average amplitudes of the FPs recorded by the gMμE-MEAs were significantly larger than those reported in two earlier publications by Langhammer et al 2122,. using substrate integrated planar electrode based MEA with a surface area of 314  μm 2  2122.…”
Section: Resultscontrasting
confidence: 57%
See 3 more Smart Citations
“…A small fraction of recorded individual gMμEs comprised FPs that were most likely generated by a number of adjacent myotubes. It should be noted that the average amplitudes of the FPs recorded by the gMμE-MEAs were significantly larger than those reported in two earlier publications by Langhammer et al 2122,. using substrate integrated planar electrode based MEA with a surface area of 314  μm 2  2122.…”
Section: Resultscontrasting
confidence: 57%
“…In contrast to the extensive use of substrate integrated MEA devices in neuroscience and cardiology research only two published papers have examined the use of MEA for in vitro skeletal myotube research. In these studies Langhammer et al 2122. demonstrated that substrate integrated planar MEA, with a surface area of 314 μm 2 , record multiphasic spontaneous FPs from rat cultured myotubes with an average amplitude of 100 μV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurement of the electrophysiological properties of cell types such as neurons, cardiomyocytes and skeletal muscle permits direct functional assessment of these cells in real time. [25][26][27] Electrical impedance measurements are attractive as a means to measure cell viability in a continuous and non-invasive manner, 28 and the use of microelectrodes could also be implemented for measurement of a wide variety of relevant metabolites such as lactate. 29 In addition, application of technologies designed to measure physical displacement, such as exible posts 30 or microscale cantilever arrays, 31 could facilitate measurement of force generation in cardiac, skeletal and smooth muscle tissues, providing analytical assessment of physical maturation within multi-organ models.…”
Section: Multi-organ In Vitro Modelsmentioning
confidence: 99%